Comparative study of gelatin methacrylate hydrogels from different sources for biofabrication applications. (21st August 2017) - Wang, Zongjie; Tian, Zhenlin; Menard, Fredric; Kim, Keekyoung
Abstract: Gelatin methacrylate (GelMA) hydrogel is a promising bioink for biofabrication applications due to its cost-effectiveness, ease of synthesis and biocompatibility to allow cell adhesion. However, the GelMA synthesized from a widely used porcine skin gelatin has a thermal gelation problem at room temperature. Here, we present thermally stable GelMA hydrogels at room temperature while maintaining the mechanical and biological properties comparable to porcine GelMA. The novel GelMA hydrogels were synthesized from fish skin and cold soluble gelatin. We systematically characterized the properties of the GelMA hydrogels from different sources. The properties include the degree of methacrylation, compressive Young's modulus, mass swelling ratio, viscosity, and cell adhesion and proliferation in 2D and 3D microenvironments. It has been found that the cold soluble GelMA was comparable to the porcine skin GelMA but could offer low viscosity and thermal stability at room temperature. We performed a droplet generation experiment to demonstrate the benefit of using the cold soluble GelMA for biofabrication. The cold soluble GelMA showed a more reliable and stable droplet fabrication process. Taken together, the cold soluble GelMA is a promising bioink solution and may greatly benefit the research in biofabrication.